Genes on chromosomes 4, 9, and 19 involved in 11q23 abnormalities in acute leukemia share sequence homology and/or common motifs. - Nakamura, T (1993)
Chromosome translocations involving band 11q23 are associated with human acute leukemias. These translocations fuse the ALL-1 gene, homolog of Drosophila trithorax and located at chromosome band 11q23, to genes from a variety of chromosomes. We cloned and sequenced cDNAs derived from transcripts of the AF-4 and AF-9 genes involved in the most common chromosome abnormalities, t(4:11)(q21:q23) and t(9:11)(p22:q23), respectively. Sequence analysis indicates high homology between the AF-9 gene protein product and the protein encoded by the ENL gene fused to ALL-1 in (11:19) chromosome translocations. AF-4, AF-9, and ENL proteins contain nuclear targeting sequences as well as serine-rich and proline-rich regions. Stretches abundant in basic amino acids are also present in the three proteins. These results suggest that the different proteins fused to ALL-1 polypeptide(s) provide similar functional domains.